Towards good governance: a south Asian perspective - Jain, R.B. (2009)
South Asia has long been a neglected area of study, primarily because it has been a region of great deprivation, want and misery, seemingly far from the mainstream of international activity except occasionally in the news as a theatre of politics in the Cold War era. it is also known as one of the most misgoverned areas of the world. Indeed, as a well known Bangladeshi scholar Rehman Sobhan has said: "South Asia is united by a common thread of `misgovernance'. In recent years, however, the wave of democratization has swept away some of the military/authoritarian and traditional polities in the region. This change together with the endemic ethnic conflicts and violence which have dogged practically every country of the region and the emergence of India as a country moving towards a rapid economic and industrial growth amongst other countries of South Asia have aroused the interest of scholars in this region. After discussing the various interpretation of the concept of "Good Governance", the paper aims to discuss some of the important challenges faced by the South Asian countries in revamping their administrative systems in order to discern the emerging perspective of "good governance" in South Asia, as distinct from its Western concept. (Reproduced).
Keywords: Good governance - South Asia; Public administration - South Asia; Public administration